(untitled) (Research, Society and Development, 2022)
Rye (Secale cereale L.) is a crop that has dual aptitude of use, where in addition to the production of grains it can be used to cover the soil, as it has a high C / N ratio of the straw that can assist in the control of plants weed. Thus, this work aims to evaluate through metanalytical models, whether rye when used as a cover crop decreases the incidence of weeds in the area in the subsequent crop, and to estimate the likelihood of decrease when compared to fallow. A search was carried out in the “Google Scholar” database using the terms: “rye AND weed”, using works in English or Portuguese published between the years 2015 and 2020, which followed the pre-established inclusion criteria. In this way, 11 publications were included, totaling 26 studies. The results show that, on average, the reduction in weed biomass provided by rye can vary from 54.6% to 79.6% when compared to fallow and that high sowing density of rye does not provide the greatest weed control.